Annalisa. Il vortice enciclopedico - Garbelli, Francesco (Scenari, 2024)
In this paper, firstly I discuss Umberto Eco’s notion of encyclopedia, with particular reference to the definition of a metalanguage: I claim that in an encyclopedic format every sign is to be understood as a token in translational relation with other tokens, and that every interpretation is to be understood as a use of tokens. Secondly, I confront encyclopedia with the Weltanschauung of pop culture, in order to show the mutual dependence between them. Thirdly, I observe that mass medialized tokens are those which offer the possibility to be used as metalanguage to the largest number of encyclopedic users and that they don’t even censor the element of pleasure that is involved in semiosis and is otherwise often silenced by elitist metalinguistic tokens. Fourthly I focus on popular music tokens and I take Annalisa Scarrone’s album E poi siamo finiti nel vortice as a case study in order to test my previous theoretical statements and develop some other remarks about the interplay of backing track and voice creating the idea of vortex, that can be seen as the proxy which listeners can use to frame semiotic activities. As a result, such a proxy displays that semiosis relies on the ‘already said’ which is stocked in encyclopedia and selected by a preliminary cut, to which user’s voice has to arrange itself in order to produce both a ‘classical’ subject (individual vocality, as opposed to backing track) and a ‘synoptic’ subject (the overall voice of the song, the principle of the vortex); and that pleasure is involved as the effect of participation in the making, as it combines personal and impersonal instances resulting in a satisfying appropriation of signs to deliver an expression. In conclusion, I draw attention to the ethical dimension of the notion of encyclopedia, for it allows everyone in the community to appropriate and expand sense.